2020
DOI: 10.1088/1361-6528/ab8084
|View full text |Cite
|
Sign up to set email alerts
|

Boosted photoresponsivity using silver nanoparticle decorated TiO2 nanowire/reduced graphene oxide thin-film heterostructure

Abstract: Here, we report on the fabrication and use of a silver (Ag) nanoparticle (NP) decorated TiO2 nanowire (NW)/reduced graphene oxide (RGO) thin-film (TF) heterostructure as a UV detector, using a controlled method called the glancing angle deposition technique. Transmission electron microscope images show Ag NPs (size 7–13 nm) covering the entire surface of the TiO2 NWs. A high absorption as well as photoluminescence for the Ag NP-TiO2 NW/RGO TF sample reveals the generation of a large number of electron–hole pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The scattering of the light photons and their reabsorption by the neighboring semiconductor increases the probability of light utilization, potentially increasing the light-harvesting properties. [50,51] Finally, photothermal heating following plasmon decay can also contribute to photocatalytic activities by increasing the local temperature close to the surface (catalytic sites). [52,53]…”
Section: E L S E E Dsmentioning
confidence: 99%
“…The scattering of the light photons and their reabsorption by the neighboring semiconductor increases the probability of light utilization, potentially increasing the light-harvesting properties. [50,51] Finally, photothermal heating following plasmon decay can also contribute to photocatalytic activities by increasing the local temperature close to the surface (catalytic sites). [52,53]…”
Section: E L S E E Dsmentioning
confidence: 99%
“…Moreover, vertical NWs array has the ability to trap more incident photons and may enhance the photon absorption [35]. Moreover, from the XRD (figure 4) it is observed that the crystallite size is decreased in case of the axial NiO/β-Ga 2 O 3 HS NW sample for which generation of more electron-hole pairs are being observed [36]. Using the Tauc's equation ( ( ) )…”
Section: Optical Analysismentioning
confidence: 99%
“…Figure 5b,d,f present a Log (I)-V between the forward and reverse biases of the composite structures. The rectifying nature of the TiO 2 /rGO heterojunction and an increase in the asymmetry between the forward and reverse biases is highlighted more for the Ti-TiO 2 -rGO-1h structure, as presented in Figure 5b; for the Ti-TiO 2 -rGO-2h and Ti-TiO 2 -rGO-3h structures, a slight rectification behavior appeared (Figure 5d,f) [37]. In order to evaluate the characteristics of the TiO 2 /rGO junction, the thermionic emission relation from the current-voltage was used [38].…”
Section: Optical and Electrical Propertiesmentioning
confidence: 90%